Dramaturgi dalam Keluarga Remarriage di Kota Probolinggo (Laboratorium Sosiologi FISIP Universitas Jember, 2023)
Families are formed by marriage between a man and a woman and expect to give birth to a generation called children. Generally, individuals expect to marry only once in their lives, but marriage is sometimes not guaranteed. Several reasons have opened up the possibility of individuals experiencing more than one marriage. By using qualitative research and a phenomenological approach, researchers describe the various life experiences that have been experienced by several remarriage families in Probolinggo City. Erving Goffman's Dramaturgy Theory is used in this study to explain the role of dramaturgy roles that have been carried out by remarriage families. The different roles between the front stage and the back stage are forced to do so that they can meet the expectations of society towards remarriage families. Each family member will be an actor in the drama played. In this drama, all family members will play the roles of husband, wife, biological children, stepchildren who are in a harmonious relationship. The visuals seen by society contrast with the factual circumstances experienced by remarriage families.